Circulating Exosomal miR-144-3p from Crohn's Disease Patients Inhibits Human Umbilical Vein Endothelial Cell Function by Targeting FN1. (2nd June 2022) - Qu, Peng; Xie, Xiaoran; Chi, Jingshu; Liu, Xiaoming; Liu, Peng; Luo, Ju; Li, Huan; Cheng, Sha; Xia, Xiujuan; Chen, Xiong; Xu, Canxia
Abstract : Background . Crohn's disease (CD) is a chronic nonspecific inflammatory disease with unknown pathogenesis and vascular changes associated with the progression of CD. Many studies have shown that miRNAs participate in the development of CD. However, the effect of miRNAs in circulating exosomes on vascular endothelial cells in CD has not been investigated. Our study is aimed at identifying the differential miRNAs in circulating exosomes in CD and exploring their potential roles in human umbilical vein endothelial cells (HUVECs). Methods . In our study, exosomes were extracted from circulating blood to identify differential miRNAs. After in vitro transfection of HUVECs with miR-144-3p mimics and inhibitors and the corresponding controls, cell counting kit-8, wound healing, Transwell migration, and tube formation assays were performed to study the viability, migration, and angiogenesis of HUVECs. Furthermore, bioinformatics analysis was used to predict miRNA targets. Western blotting was used to determine protein expression. In addition, exogenous supplementation with the fibronectin 1 (FN1) protein rescued the effects of miR-144-3p on changes in cell function in vitro. Results . miR-144-3p was significantly increased in circulating exosomes of patients with CD compared with those in the control group. The promotion or inhibition of miR-144-3p correspondingly abolished or accelerated cell viability, migration, and angiogenesis. FN1 is a significant target of miR-144-3p, and exogenous FN1 administration improved the function of HUVECs in vitro. Conclusions . Circulating exosomal miR-144-3p from patients with active CD contributes to vascular endothelial dysfunction by affecting the gene expression of FN1 . These findings suggested that circulating exosomal miR-144-3p could be a potential biological marker for CD.